PSYCHOLOGY OF AUTHOR IN “ANNE OF GREEN GABLES” NOVEL WRITTEN BY LUCY MAUD MONTGOMERY - Arfiani Arfiani; Indah Wardaty Saud (Universitas Muhammadiyah Gorontalo, 2019)
The objective of this research is to analyze the psychology of Lucy Maud Montgomery as a write which is reflected in her novel entitled Anne of Green Gables. The technique of collecting data is data documentation technique that is a record of events that has passed. The documentation covers the content of Montgomery’s novel and her biography. The approach in analyzing the novel is psychological approach. The result is Lucy Maud Montgomery as the author and Anne as the main character in the novel have imaginative personality which belong to practical imaginative type, has desire to be appreciated, and loneliness. Besides, loneliness gives the impact towards Lucy Maud Montgomery in creating her personalityin writing her works.